Pros and Cons of the Debate on the Implementation of the Latest Pencak Silat Regulations in Indonesia - Nur Subekti; Rony; Deny Pradana Saputro; Cahniyo Wijaya Kuswanto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to explore the pros and cons of the discourse on the implementation of the latest pencak silat regulations passed by PERSILAT in 2021. The research method used was a mixed approach with a sequential exploratory model, beginning with qualitative analysis through documentation of public comments on social media, followed by a quantitative survey of administrators, coaches, athletes, and academics focused on pencak silat. The results indicate that the majority of respondents disapproved of the new rules. They argued that the rules failed to meet the expectations of practitioners, imitated other martial arts systems and risked diminishing the cultural uniqueness of pencak silat. When considering the pros and cons, this study revealed that those in favour of the new rules appreciated the efforts to modernise and internationalise pencak silat, particularly through technological integration, such as the use of the Video Assistant Referee (VAR) system. Meanwhile, the contra group argued that the new regulations made the competition more complex and unsafe, and detached it from its traditional identity. Quantitatively, 83.4% of respondents favoured the old 2013 rules, while only 16.6% supported the new ones, emphasising a strong preference for preserving the sport's originality. These findings highlight the importance of a thorough review and stakeholder engagement before the new regulations are implemented more widely, particularly in Indonesia.